The Influence Of Good Corporate Governance, Financial Performance And Company Business Strategy On Dividend Policy - Sumantri, Muhammad Bayu Aji; Amalia, Shendy (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to investigate the impact of Good Corporate Governance, Financial Performance, and Business Strategy on a company's dividend policy. The subjects of this research encompass companies in the banking sector that are listed on the Indonesia Stock Exchange, covering the observation period from 2018 to 2022. The Good Corporate Governance variables are approximated using Independent Commissioners and Institutional Shareholders. Meanwhile, the Financial Performance variables are represented by NPL, ROA, and Tobin's Q. Alongside the Corporate Business Strategy variables, the proxies employed consist of Company Size and Debt to Asset Ratio. Dividend per share serves as the dependent variable proxy. Employing the method of multiple regression analysis, this study concludes that Tobin's Q, ROA, and Institutional Shareholders significantly impact the company's dividend policy.